Hyperproliferative hepatocellular alterations after intraportal transplantation of thyroid follicles - Dombrowski, Frank; Klotz, Luisa; Hacker, Hans Jörg; Li, Yanhua; Klingmüller, Dietrich R.; Brix, Klaudia; Herzog, Volker; Bannasch, Peter (The American journal of pathology, 2000)
The thyroid hormone 3,5,3′-triiodo--thyronine (T3) is a strong direct hepatocyte mitogen in vivo. The effects of T3 resemble those of peroxisome proliferators, which are known to induce hepatocellular tumors in rats. With the aim of studying long-term ...
Gesehen am 15.02.2019